Electromagnetically Induced Transparency Effect for Two Level Ensemble Using Multi Mode-Silicon Waveguide Coupled to Plasmonic Resonator Array (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied the electromagnetically induced transparency for a two level  ensemble interacting with two orthogonal optical modes. We have made a approach  for a multimode silicon waveguide coupled to a plasmonic resonator array. We have  shown that a simple periodic ensemble of resonant metal nanoparticles within a  dielectric waveguide supported a transparent waveguide plasmon polariton mode  for guided slow light propagation. Such systems inhert the strongly dispersive  properties of the nanoparticles embedded in the waveguide but do not succumb to  the associated absorptive losses by utilizing the system’s transparency Light  propagation through the system provided extremely strong dispersion from the  resonators, but suffers very low propagation loss by exploiting the system’s  transparency. Dispersion is controllable by tuning the coupling strength of localized  plasmon and waveguide modes. We have found that atomic electromagnetically  induced transparency occurred for a non zero pump field allowing mutual coupling  of all states and induced destructive quantum interference of the probe field’s  absorption via the transition. The obtained results were found in good agreement  with previously obtained results.